Characteristics of Kappaphycus alvarezii carrageenan from different cultivation locations - Irman Irawan (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This research aimed to determining physical and chemical characteristics of Kappaphycus alvarezii carrageenan from Bontang and and East Kutai. The method carrageenan extraction process was carried out in the water bath equipped by stirrer. Furthermore, the extraction process was conducted with a constant ratio of seaweed weight to distilled water volume (10:100 g/ml) at 75oC for an hour. The extract was precipitated in Potassium hydroxide (KOH) 6%, potassium chloride 0.2% and ethanol which increase the speed of carrageenan formation. They were dried in an oven at 60oC for 24 hours. The chemical carrageenan test results showed the water content seaweed from Bontang (12.7%), East Kutai (12.74%), ash content seaweed from Bontang (32.49 %) and East Kutai (33.80%), pH seaweed from Bontang (8.58) and East Kutai (8.52); the physical characteristic results showed the fiber seaweed from Bontang (7.45 %) and East Kutai (9.78%), the viscocity of carrageenan seaweed from Bontang (16.38 cPs) and East Kutai (11.19 cPs) and gel strength of carrageenan seaweed from Bontang (408.00 g/cm2) and East Kutai (411.67 g/cm2). This physical and hemical characteristics of Kappaphycus alvarezii, meet the quality standard regulated by FAO, FCC and EEC